Cementation of sand soil by microbially induced calcite precipitation at various degrees of saturation - Cheng, L.; Cord-Ruwisch, R.; Shahin, Mohamed (NRC Research Press, 2013)
A newly emerging microbiological soil stabilization method, known as microbially induced calcite precipitation (MICP), has been tested for geotechnical engineering applications. MICP is a promising technique that utilizes the metabolic pathways of bacteria to form calcite precipitation throughout the soil matrix, leading to an increase in soil strength and stiffness. This paper investigates the geotechnical properties of sand bio-cemented under different degrees of saturation. A series of laboratory experiments was conducted, including sieve analysis, permeability, unconfined compressive strength, consolidated undrained triaxial, and durability tests. The results indicate that higher soil strength can be obtained at similar CaCO3 content when the treatment is performed under a low degree of saturation. The experimental results are further explained with a mathematical model, which shows that the crystallization efficiency, i.e., actual volume of crystals forming at the contact point where they contribute the most to strength, can be calculated from the degree of saturation and grain size. Fine sand samples exhibited higher cohesion, but lower friction angle than coarse sand samples with similar CaCO3 content. The results also confirm the potential of MICP as a viable alternative technique for soil improvement in many geotechnical engineering applications, including liquefiable sand deposits, slope stabilization, and subgrade reinforcement. The freeze–thaw and acid rain resistance of MICP-treated sand has also been tested.